“SPORT AND PHYSICAL ACTIVITY ENTREPRENEUR” EXPERIMENTAL TEACHING SPORT ADMINISTRATION AND A JOB ALTERNATIVE FOR THE STUDENT OF PHYSICAL EDUCATION AND SPORTS (Fiep Bulletin - online, 2014)
The following paper was elaborated under significant experiential methodology, and application, as a unit in the department of Administration and Organization of Physical Education for 20 years at the University of Los Andes (UL A), and the backdrop of the state application Mérida and some cities in the country with updates and changes as needed physical activity sports. Its main objective is to demonstrate how to encourage students and train them in the business aspect, as entrepreneurs, creating their own Sport and Physical Activity Services Microenterprise (PASM ), individual type, with projected future change kind of personal signature, corporation or company. The PASM project works for a regular academic semester, between the student, the teacher and three consultants, one legal, one an accountant or area specific service that students choose to create the PASM , in this process of future PASM achieves certain build and strengthen management skills, be an agent of change, contributing to economic and social development of their communities and the country, treating the teacher as much as possible to develop in students an entrepreneurial spirit, through methodologies based on the constructivism and learning by doing. The student observes, analyzes and makes contact with the real needs of their environment or sports physical activity, using a feasibility study, a market survey, a study of different resources and considering also the external variables such as political, economic, social, among others, and then start more precisely its inclination and personal goals, for which you must obtain basic management tools, such as: marketing and sales, operations, communications, economics, budget, finance and human resource management among others. The results have been satisfactory, given that it has complied with the program, where students have achieved their purpose, creating a considerable amount of PASM and several of these are operating today.
Keywords: entrepreneur; small business; sports services; physical activity